Dynamic Manugraphy as a Promising Tool to Assess the Outcome of Limited Aponeurectomy in Patients With Dupuytren's Contracture - Garkisch, Angelina; Mittlmeier, Thomas; Kalpen, Axel; Mühldorfer-Fodor, Marion; Fischer, Dagmar-C.; Wichelhaus, Alice (Frontiers in Medicine, 2021)
Background: Dupuytren's contractures interfere with physiological gripping. While limited aponeurectomy is an accepted treatment modality to restore finger mobility, methods to objectify the functional outcome beyond determination of the range of motion are scarce. Methods: Patients with Dupuytren's contracture being scheduled for unilateral limited aponeurectomy were investigated. The DASH-score and the flexion contracture for the fingers were registered prior to surgery as well as 3 and 6 months afterwards. At the same time, dynamic manugraphy for simultaneous recording of the grip pattern and forces generated by the affected hand and anatomic areas (i.e. thumb, fingers, and palm) were performed. All findings obtained during the follow-up period were compared to the situation at baseline. Comparison between paired samples was done using Wilcoxon rank test. All p-values are two-sided and p < 0.05 was considered to be significant. Results: Out of 23 consecutively enrolled patients, 19 completed the follow-up examinations. Manugraphy confirmed the impairment of physiological gripping with concomitant pathological load distribution at base line. Limited aponeurectomy significantly reduced the flexion contractures. The DASH-score remained at an excellent level in one patient and indicated improvement and worsening of the condition in 11 and 7 patients, respectively. Six patients had lower grip force at t6 compared to the preoperative condition. In four of those, the DASH-score improved while it turned worse in two of them. The force of surgically treated fingers remained unchanged in three patients while it was improved and worsened in half of the remaining patients, respectively. Manugraphy revealed physiological gripping by enlargement of contact area and higher force transmission by the fingertips in 10 of 12 patients with constant or even improved DASH-score and in 3 of 7 patients with a worsened DASH-score. Conclusions: Assessing the reduction of flexion contracture and grip force alone is not sufficient to comprehensively reflect the functional outcome of aponeurectomy for Dupuytren´s disease. Visualizing the physiological grip pattern provides an additional tool to objectify the success of surgical treatment.